Development and validation of a scale to measure L2 motivation in Australian secondary students - James Toohey; Michael D. Carey; Peter R. Grainger (Social Sciences and Humanities Open)
This study investigates the validity and reliability of a newly developed L2 motivation survey scale tailored for Australian secondary students, using both whole model and component-level Rasch analyses. Dörnyei's L2 Motivational Self System (L2MSS) framework was employed, encompassing the dimensions of Ideal L2 Self, Ought-to L2 Self, Anti-Ought-to Self, and L2 Learning Experience. Both the entire model and each individual component were analysed using Rasch model analysis to evaluate their reliability and validity. The whole model analysis confirmed the unidimensionality of the scale, demonstrating strong reliability indices and alignment between person ability and item difficulty. Each component was further analysed individually to provide additional insights into their specific performance within the Rasch framework. Findings supported the inclusion of the ‘anti-ought-to’ dimension in monolingual contexts. The component analyses highlighted both strengths and areas for improvement within the scale, particularly for items that displayed potential multidimensionality. The findings highlight the importance of context-specific validation, with implications for educational practices that target L2 motivation in agentic, monolingual-dominated environments. Future research should further refine the L2MSS framework, investigate the influence of cultural dimensions, and explore the survey's applicability across diverse educational settings.